2005
DOI: 10.1097/01.moh.0000177828.85904.70
|View full text |Cite
|
Sign up to set email alerts
|

Massive blood transfusion for trauma

Abstract: Injury is a major public health and medical system problem. Progress in basic science, clinical care, and the development of better hemorrhage control devices are all improving outcome for massively transfused patients. Investment in trauma care and supporting blood supply systems is highly cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 47 publications
0
37
0
1
Order By: Relevance
“…Enhanced insight into the pathogenesis of posttraumatic SIRS has lead to less liberal blood transfusion habits. 59 It has been shown that blood transfusion itself induces a host immunoactivation with possible increase or even induction of SIRS and MOF. 60 -63 Furthermore the use of RBC transfusions is associated with a considerable risk of infections and hemolytic transfusion reactions.…”
Section: Therapeutic Consequencesmentioning
confidence: 99%
“…Enhanced insight into the pathogenesis of posttraumatic SIRS has lead to less liberal blood transfusion habits. 59 It has been shown that blood transfusion itself induces a host immunoactivation with possible increase or even induction of SIRS and MOF. 60 -63 Furthermore the use of RBC transfusions is associated with a considerable risk of infections and hemolytic transfusion reactions.…”
Section: Therapeutic Consequencesmentioning
confidence: 99%
“…In search for effective treatments, efforts have been made to evaluate outcomes from transfusion of blood products, such as fresh whole blood, fresh frozen plasma (FFP), cryoprecipitate, and red blood cells (RBC). Recent published retrospective studies suggested potential benefits of transfusion of a higher ratio of fibrinogen to red blood cell unit ratio in trauma patients [6,7,[64][65][66][67][68][69][70][71][72].…”
Section: Fibrinogen Supplementationmentioning
confidence: 99%
“…Despite aggressive fluid replacement, the patient's hemodynamic status remained time temperatures often exceed 49ºC [120ºF]), ensuring shelf life, and coordinating resupply caused major difficulties for our blood bank in addition to the normal complications associated with maintaining stored blood. 5 Indications for the use of fresh whole blood (FWB) have been reported. Jevtic et al 6 (Figure 2).…”
mentioning
confidence: 99%